2022
DOI: 10.1007/s10064-022-02817-6
|View full text |Cite
|
Sign up to set email alerts
|

Recycled aggregates derived from excavation materials—mechanical performance and identification of weak minerals

Abstract: The present study investigates the mechanical performance of recycled aggregates derived from excavation materials (REM). REM is blended with different quantities of recycled phyllite materials (RPM) and is investigated by Los Angeles (LA) and micro-Deval (MD) tests. X-ray diffraction (XRD) and acid solubility test are performed on the pulverized fractions < 1.6 mm obtained from the LA and MD tests to assess the respective degree of fragmentation and wear of mineral components. The results of the materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…For RCZ0, the WA obtained is higher than 0.3% reported for similar material in the study [30]. Studies that have investigated the performance of RCSA reported WA values within the margin 4-13% [20,22].…”
Section: Physical Propertiescontrasting
confidence: 66%
See 1 more Smart Citation
“…For RCZ0, the WA obtained is higher than 0.3% reported for similar material in the study [30]. Studies that have investigated the performance of RCSA reported WA values within the margin 4-13% [20,22].…”
Section: Physical Propertiescontrasting
confidence: 66%
“…Regarding the LA for RCZ0, other studies have reported stabilized results for excavation materials within the range of 24-28% [30,31]. The LA for RCZ50 also show the optimal intermix of recycled aggregates RCZ and excavation materials.…”
Section: The Los Angeles and Micro-deval Performancementioning
confidence: 87%
“…The LA determines the resistance to fragmentation, whereas MD evaluates wear resistance. The LA values for REM and RPM were 28% and 26%, respectively, whereas the MD was reported to be 6% and 26% [14]. The MD results varied significantly between REM and RPM.…”
Section: Water Absorption (%) En 1097-6mentioning
confidence: 92%
“…The complete test setup with the chamber filled with water is shown in Figure 3h, and Figure 3i shows the computer for data collection. tively, whereas the MD was reported to be 6% and 26% [14]. The MD results varied significantly between REM and RPM.…”
Section: Water Absorption (%) En 1097-6mentioning
confidence: 94%
See 1 more Smart Citation